Production of Bioethanol from Bamboo Powder Via Dilute Sulphuric Acid-Sodium Hydroxide Pre-Treatment and Simultaneous Saccharification and Fermentation (SSF) - Zakaria, Muhammad Hairul Zakwan; Che Pa, Nasrul Fikry (Journal of Advanced Industrial Technology and Application, 2023)
Biofuel is a new type of fossil fuel that is usually derived from biomass waste. Studies found that lignocellulosic biomass (LCB) has the potential to become a new source for biofuel production. Even so, it is a challenging process to fully utilise the potential of cellulose in LCB due to the chemical structures of the lignocellulose biomass. Pre-treatment of LCB is one of the most crucial steps in converting LCB into bioethanol products. In this study, the potential of production for bioethanol from Bambusa Wray bamboo species via dilute sulphuric acid (H2SO4) and sodium hydroxide (NaOH) pre-treatment and simultaneous saccharification and fermentation (SSF) was explored. The effect of H2SO4 and NaOH pre-treatment on the chemical structure of Bambusa Wray was studied using Fourier-transform Infrared (FTIR) analysis. The impact of different concentrations of H2SO4 during pre-treatment towards the concentration of glucose produced was investigated using the dinitrosalicylic acid (DNS) method. The availability and the amount of bioethanol produced during the SSF were analysed using FTIR. It was found that, a noticeable decrease in the intensities of absorption peaks can be observed at 1604, 1462 and 1242 cm-1 after being treated with sequential acid-alkaline pre-treatment. It indicates the removal of lignin from the sample. It was reported that 4% H2SO4 + 5% NaOH produces the highest glucose concentration, 6.491 mg/ml, compared to untreated bamboo, which only produces 1.158 mg/ml. At the end of the study, bioethanol was absent in the sample due to the availability of yeast. Overall, it was proven that Bambusa Wray is capable of producing enough glucose for production of bioethanol.